(untitled) (Castilla. Estudios de Literatura, 2012)
The linguistic materiality, the materiality without materia, as called Derrida (2001) referring to Paul de Man, displaces the conventional act of reading, and even the same statute of literature. It implies that the resulting positions of the act of reading are inscribed in the space of the ethical and political action with respect to the same done reading. This materiality is not only the condition of possibility of reading, but at the same time and inextricably of its impossibility. In this work we want to show the treatment of this materiality by Saussure, Foucault and Deleuze in several heterogeneous writings each other, but that however converge in this way to read the texts. The lesson of reading that is deducted from these approaches can be understood as an act of sabotage, as an act of political challenge to the positions and inscriptions resulting from the act of literature.